Analisis Efektivitas Sistem Penerimaan Peserta Didik Baru Berbasis Online di MAS YPP Jamanis - Robihatil Milah; Gita Puspita; Usup Purkon; Acep Wildan Mubarok; Sobirin Sobirin (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2024)
This study aims to analyze the effectiveness of the online admission system at MAS YPP Jamanis. Modern education today is increasingly adopting information technology, including in the process of admitting new students. Therefore, it is important to evaluate the extent to which the effectiveness of the online-based new student admission system at MAS YPP Jamanis.  This research method is a qualitative approach. The results found that the online-based new learner admission system is quite effective, but it still has shortcomings because there are still many people who do not know how to do online registration, as well as the promotion of online-based PPDB which is still less extensive. But further we also found that the community has been able to adjust to the new student registration system that is carried out online. Continuity of PPDB through the web.